2021
DOI: 10.3389/fpsyg.2021.594260
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Evaluations of Black and White Women’s Workplace Anger During the Era of #MeToo

Abstract: Researchers investigating gender and anger have consistently found that White women, but not White men, are evaluated unfavorably when experiencing anger in the workplace. Our project originally aimed to extend findings on White women’s, Black women’s, and White men’s workplace anger by examining whether evaluations are exacerbated or buffered by invalidating or affirming comments from others. In stark contrast to previous research on gender stereotyping and anger evaluations, however, results across four stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Research by Livingston et al (2012) finds that Black women leaders were favorably evaluated when enacting agentic behaviors. McCormick-Huhn and Shields (2021) extend this finding by examining how angry Black women are evaluated at work. In two studies (Studies 2 & 3), they compared reactions to angry Black women with reactions to angry white men.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Research by Livingston et al (2012) finds that Black women leaders were favorably evaluated when enacting agentic behaviors. McCormick-Huhn and Shields (2021) extend this finding by examining how angry Black women are evaluated at work. In two studies (Studies 2 & 3), they compared reactions to angry Black women with reactions to angry white men.…”
Section: Discussionmentioning
confidence: 77%
“…Specifically, the design we use in Study 2, which crosses the gender of the worker with the emotion they are expressing-anger vs. sadness vs. muted emotion -is the only design that can test whether anger is penalized or sadness is rewarded. Previous work examined the anger-status relation by either comparing angry workers to sad workers (e.g., Tiedens, 2001), comparing angry men workers to angry women workers (e.g., McCormick-Huhn and Shields, 2021), or by comparing angry workers to emotionless workers (e.g., Brescoll and Uhlmann, 2008). While these comparisons provide useful information, they cannot determine whether workers who express anger are penalized, or whether workers who express other emotions (e.g., sadness) are rewarded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The intersection of race and femininity is a complex and multifaceted topic that has received increasing attention in recent years. Research has shown that the actions of women of color are perceived differently than those of White women in the same contexts ( McCormick-Huhn and Shields, 2021 ). Women of color are more likely to experience sexual harassment, for example, and may be more vulnerable to other forms of violence and abuse due to the juxtaposition of their race and gender identities ( Cassino and Besen-Cassino, 2019 ).…”
Section: Introductionmentioning
confidence: 99%